Clinical testing of implanted pacemakers. Issue 2 (March 1971) - Sowton, Edgar; Gray, Kenneth
Abstract : The function of implanted pacemakers was assessed at a special pacemaker clinic at intervals of three to six months. Measurements of the basic discharge rate of the pacemaker were made and the waveform was recovered from skin electrodes and displayed on an oscilloscope screen. The impulse was photographed from the screen and subsequent waveform analysis was carried out. Reproducible results were obtained for measurements of peak amplitude and impulse duration provided unipolar electrodes were in use and the patients were studied in the same position. The range of variation of the measurements during the lifetime of different models of normally functioning pacemakers is given. Test measurements taken before failing pacemakers were removed have been correlated with the subsequently established cause of failure and the waveform analysis test has been shown to be clinically reliable. The value of the test depended largely upon the type of pacemaker but it correlated well with rate changes in pacemakers designed to slow as battery exhaustion developed. The clinical value of waveform analysis tests is in the diagnosis of exit block, electrode failure, and premature battery exhaustion and in determining the optimum time for pacemaker replacements. The indications for replacement of pacemakers at the National Heart Hospital are given. Initial experience with an automatic analyser with three types of pacemaker shows that rapid measurements of the waveform parameters can be achieved with accuracy.